Formation of inter-organizational relationships on the example of small enterprise = Kształtowanie relacji międzyorganizacyjnych na przykładzie działalności małego przedsiębiorstwa - Danielak, Wiesław (Zielona Góra: Faculty of Economics and Management Press)
Inter-organizational relationships are crucial for the functioning and development of the company, and appropriately shaped give the value of the company and its cooperating entities. The aim of the article is to show the possibility of formation of inter-organizational relationships as part of a three-dimensional model including selected elements of human capital, structural and relational. Based on studies of literature and conducted analysis of the activities of a small enterprise there were shown measures conducive to the formation of inter-organizational relationships.
Keywords: relacje międzyorganizacyjne; kapitał ludzki; kapitał strukturalny; kapitał relacyjny; inter-organizational relationships; human capital; structural capital; Relational capital